Valproate and retinoic acid in combination with decitabine in elderly nonfit patients with acute myeloid leukemia: results of a multicenter, randomized, 2 × 2, phase II trial - Lübbert, Michael; Grishina, Olga; Schmoor, Claudia; Schlenk, Richard Friedrich; Jost, Edgar; Crysandt, Martina; Heuser, Michael; Thol, Felicitas; Salih, Helmut R.; Schittenhelm, Marcus M.; Germing, Ulrich; Kuendgen, Andrea; et al. (Journal of clinical oncology, 2019)
PURPOSEDNA-hypomethylating agents are studied in combination with other epigenetic drugs, such as histone deacetylase inhibitors or differentiation inducers (eg, retinoids), in myeloid neoplasias. A randomized, phase II trial with a 2 × 2 factorial design was conducted to investigate the effects of the histone deacetylase inhibitor valproate and all-trans retinoic acid (ATRA) in treatment-naive elderly patients with acute myeloid leukemia (AML).PATIENTS AND METHODSTwo hundred patients (median age, 76 years; range, 61-92 years) ineligible for induction chemotherapy received decitabine (20 mg/m2 intravenously, days 1 to 5) alone (n = 47) or in combination with valproate (n = 57), ATRA (n = 46), or valproate + ATRA (n = 50). The primary endpoint was objective response, defined as complete and partial remission, tested at a one-sided significance level of α = .10. Key secondary endpoints were overall survival, event-free survival, and progression-free survival and safety.RESULTSThe addition of ATRA resulted in a higher remission rate (21.9% with ATRA v 13.5% without ATRA; odds ratio, 1.80; 95% CI, 0.86 to 3.79; one-sided P = .06). For valproate, no effect was observed (17.8% with valproate v 17.2% without valproate; odds ratio, 1.06; 95% CI, 0.51 to 2.21; one-sided P = .44). Median overall survival was 8.2 months with ATRA v 5.1 months without ATRA (hazard ratio, 0.65; 95% CI, 0.48 to 0.89; two-sided P = .006). Improved survival was observed across risk groups, including patients with adverse cytogenetics, and was associated with longer response duration. With valproate, no survival difference was observed. Toxicities were predominantly hematologic, without relevant differences between the 4 arms.CONCLUSIONThe addition of ATRA to decitabine resulted in a higher remission rate and a clinically meaningful survival extension in these patients with difficult-to-treat disease, without added toxicity.
Gesehen am 24.06.2020